A furnace - Fisher, Roy 1930-2017 (Flood Editions, 2018)
Introduction /Peter Robinson --A note on the text --Introit: 12 November 1958 --Calling --The return --Authorities --Core --Colossus --The many --On fennel-stalks --Appendix:They come home --Preface (1986) --Author's notes --Notes
Keywords: English poetry / 20th century; English poetry; Poetry